Application of validated mathematical model of composting process for study the effect of air flow rate on process performance - Mustafić, Nesib; Petrić, Ivan; Karić, Ervin (Journal of Engineering & Processing Management, 2017)
The objectives of this study were to develop and validate the mathematical model (kinetic and reactor model) of composting process, as well to used validated model in order investigate the effects of the air flow rate on organic matter conversion, carbon dioxide concentration and mixture temperature. The mathematical model incorporated two microbial populations that metabolized composting material which was split into two different fractions according to its degradability (easily-degradable and hardly-degradable). Comparisons of simulation and experimental results for five dynamic state variables demonstrated that the model has very good predictions of the composting process. Simulations with validated model showed that among three dynamic state variables (organic matter conversion, carbon dioxide concentration, mixture temperature), carbon dioxide concentration is the most sensitive while organic matter conversion is the least sensitive to the change of air flow rate.